The diagnosis and management of congenital pulmonary valve stenosis - Mitchell, B; Mhlongo, M (SA Heart Journal, 2018)
Congenital pulmonary stenosis (PS) is one of the most prevalent congenital cardiac abnormalities. A thorough assessment is needed to determine which of the many patients born with PS, will need intervention and further management, and which will only need routine follow up. Accurate non-invasive assessment of the severity of the PS at transthoracic echocardiography is therefore important. This article will discuss and delineate the diagnostic approach to, and management of, a patient with congenital PS.